Calcium, Dopamine and Neuronal Calcium Sensor 1: Their Contribution to Parkinson’s Disease - Catoni, Cristina; Calì, Tito; Brini, Marisa (Frontiers in Molecular Neuroscience, 2019)
Parkinson's disease (PD) is a debilitating neurodegenerative disorder characterized by loss of dopaminergic neurons in the substantia nigra pars compacta. The causes of PD in humans are still unknown, although metabolic characteristics of the neurons affected by the disease have been implicated in their selective susceptibility. Mitochondrial dysfunction and proteostatic stress are recognized to be important in the pathogenesis of both familial and sporadic PD, and they both culminate in bioenergetic deficits. Exposure to calcium overload has recently emerged as a key determinant, and pharmacological treatment that inhibits Ca2+ entry diminishes neuronal damage in chemical models of PD. In this review, we first introduce general concepts on neuronal Ca2+ signalling and then summarize the current knowledge on fundamental properties of substantia nigra pars compacta dopaminergic neurons, on the role of the interplay between Ca2+ and dopamine signalling in neuronal activity and susceptibility to cell death. We have also considered the possible involvement of a “neglected” player, the Neuronal Calcium Sensor-1 (NCS-1), which has been shown to participate to dopamine receptors desensitization process. Even if its contribution in dopaminergic signaling in normal brain is well established, data supporting a direct role in PD pathogenesis are still missing. However, it is intriguing to speculate that the Ca2+-dependent modulation of NCS-1 activity could eventually counteract dopaminergic neurons degeneration.